PENYELESAIAN KONFLIK RECLAIMING DAN PENDUDUKAN TANAH DILIHAT DARI HUKUM TANAH NASIONAL: STUDI KASUS RECLAIMING DAN PENDUDUKAN TANAH ANTARA PT. AGRI ANDALAS, PT. PERKEBUNAN NUSANTARA VII DAN WARGA DESA TANAH ABANG DI DESA TANAH ABANG, KECAMATAN TALO, - Muhammad Fauzan Hidayat (Jurnal Bedah Hukum, 2017)
This research aims to know what factors that motivates the society occupying that plantation area at Tanah Abang village, District of Talo, Seluma Regency, Province of Bengkulu and efforts or patterns of conflict settlement that have been done. This research is empirical law research. This research is empirical legal research. The data is used in this research is primary data which is gathering directly from observation subject utilizing questionnaire for respondent and interview for the sources. Secondary data is gotten from literature and document study. And then, those data are analyzed in qualitative descriptive. The results arefirst, factors that motivate conflict happened is inconsistency of both company in performing the fixed rules especially about land releasing, local official mentality particularly village leader that took advantage of the situation to get individual profit, there is no apparent border either village or district, and many neglected land that cause other person inside or outside the area occupatied the land.Second, effrot or pattern that has been done to solve conflict is: outside the court that still doesn’t reach final result yet.